Penguatan Karakter Santri Berbasis Melalui Internalisasi Nilai Khalifah Fil Ard Dalam Pendidikan Islam - Yundri Akhyar; Zaitun Abidin; Supri Supri; Eli Sutrawati; Wirda Ningsih (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2026)
Strengthening students' character has become one of the primary priorities in Islamic education, particularly within Islamic boarding schools (pesantren), which play a strategic role in shaping the moral values and leadership of the younger generation. However, many students still demonstrate limited awareness in practicing social responsibility and environmental stewardship. This community service program aimed to strengthen students' character through the internalization of the Khalifah fil Ard (vicegerency on earth) values in Islamic education. The program employed a participatory approach consisting of educational seminars, group discussions, character development training, and social service activities within the pesantren environment. A total of 40 students actively participated in all stages of the program. The results indicated a significant improvement in students' understanding of the Khalifah fil Ard concept, accompanied by positive behavioral changes reflected in increased discipline, responsibility, social awareness, and environmental consciousness. Furthermore, the program encouraged students to apply Islamic leadership values in their daily lives. Therefore, the internalization of Khalifah fil Ard values can serve as an effective strategy for strengthening character education among students in Islamic boarding schools